Deformation behavior of Al-rich metallic glasses under nanoindentation. Issue 11 (November 2017) - Guo, Hui; Jiang, Chuanbin; Yang, Baijun; Wang, Jianqiang
Abstract: To clarify the deformation behavior of Al-rich metallic glasses (MGs), two kinds of Al-rich MGs (i.e. bulk and ribbon samples) with different frozen-in excess volume have been analyzed under nanoindentation. It was found that, with the decrease of frozen-in excess volume, the serration behavior becomes inconspicuous together with the increase of hardness. Further, shear transformation zones (STZs), related to the occurrence of shear banding, have been evaluated by different methods: the cooperative shearing model (CSM), the rate-jump method (RJM) and the dynamic-mechanical response (DMR). In contrast, the STZ volumes, calculated by the RJM, increase from 2.77 nm 3 in the bulk to 3.59 nm 3 in the ribbon, which are in good agreement with 2.60 nm 3 obtained from the icosahedral supercluster medium-range order structure model in Al-rich MGs. This result reflects that an intrinsic correlation exists between the formation of STZs and the medium-range orders (MROs). Moreover, the variation trend of the STZ volume was analyzed in terms of the frozen-in excess volume content.